The Mediating Role of Innovation on the Relationship Between Knowledge Management, Organizational Learning, and SME Performance - Hidayat, Muhammad (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2024)
In today's business landscape, innovation has become a critical determinant for organizational survival and competitiveness in an increasingly volatile industrial environment. Companies must strategically manage their knowledge and organizational learning while fostering an innovation-driven culture to optimize performance outcomes. Based on this rationale, the present study investigates how innovation mediates the influence of knowledge management and organizational learning on organizational performance. The research gathered data from 200 SME entrepreneurs in South Sulawesi through a structured questionnaire. Data analysis was performed using the Partial Least Squares (PLS) method. Findings reveal that both knowledge management and organizational learning exert direct, positive, and significant impacts on performance. Furthermore, both also positively influence innovation, which in turn significantly boosts performance. Notably, innovation also acts as a significant mediating mechanism between knowledge management, organizational learning, and performance in SMEs.